2009
DOI: 10.1111/j.1439-0418.2008.01352.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid assessment of the sex of codling moth Cydia pomonella (Linnaeus) (Lepidoptera: Tortricidae) eggs and larvae

Abstract: Two different methods were tested to identify the sex of the early developmental stages of the codling moth Cydia pomonella (Linnaeus) (Lepidoptera: Tortricidae) with a WZ/ZZ (female/male) sex chromosome system. First, it was shown that the sex of all larval stages can be easily determined by the presence or absence of sex chromatin, which is formed by the female‐specific W chromosome in interphase nuclei. This trait can also be used to identify the sex of newly hatched larvae but it does require care and accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…Available methods, such as emergence cages (Goffart et al, 2010), exist, but their use in the diverse woodland environments may be more difficult then, e.g., on rather uniform grasslands. Another alternative may be repeated search for larvae during the larval period and the construction of survival tables, with the larvae sex determined using up-to-date molecular methods (Fukova et al, 2009).…”
Section: Models Testedmentioning
confidence: 99%
“…Available methods, such as emergence cages (Goffart et al, 2010), exist, but their use in the diverse woodland environments may be more difficult then, e.g., on rather uniform grasslands. Another alternative may be repeated search for larvae during the larval period and the construction of survival tables, with the larvae sex determined using up-to-date molecular methods (Fukova et al, 2009).…”
Section: Models Testedmentioning
confidence: 99%
“…Additionally, a partial sequence of the C. pomonella circadian gene period (per) was acquired from GenBank [accession no. JX996071 (17)]. Hybridization probes generated from the cloned gene fragments were used for screening of the C. pomonella bacterial artificial chromosome (BAC) library.…”
mentioning
confidence: 99%
“…The 956‐bp PCR fragment from cDNA was used as a probe in Southern hybridization, resulting in hybridization signals which were twice as strong with male DNA as with female DNA. This indicated that this Cpper fragment is located on the Z‐chromosome (Fuková et al. 2009).…”
Section: Fao/iaea Coordinated Research Projectmentioning
confidence: 91%
“…Recently, one of the motifs, CpW2, was extended by sequencing of flanking regions with the aim to develop a molecular marker of the W‐chromosome. The resulting 2.74‐kb long Eco RI DNA fragment (CpW2‐ Eco RI) proved to be female‐specific by Southern hybridization and by polymerase chain reaction (PCR) testing and proved to be a reliable marker for the sex identification in codling moth samples of different geographical origin (Fuková et al. 2009).…”
Section: Fao/iaea Coordinated Research Projectmentioning
confidence: 99%